2020
DOI: 10.1021/acs.analchem.0c01604
|View full text |Cite
|
Sign up to set email alerts
|

Metal- and Affinity-Specific Dual Labeling of Cysteine-Rich Proteins for Identification of Metal-Binding Sites

Abstract: Here, using human metallothionein (MT2) as an example, we describe an improved strategy based on differential alkylation coupled to MS, assisted by zinc probe monitoring, for identification of cysteine-rich binding sites with nanomolar and picomolar metal affinity utilizing iodoacetamide (IAM) and N -ethylmaleimide reagents. We concluded that an S N 2 reaction provided by IAM is more suitable to label free Cys residues, avoiding nonspecific metal dissociation. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(57 citation statements)
references
References 75 publications
1
51
0
Order By: Relevance
“…Interestingly, the y 31 fragment derived from backbone dissociation between α- and β-domain contained three Zn 2+ , probing the higher stability of Zn–S bonds and folding of the α-domain. 14 , 56 On the other hand, fragment b 17 with four Cys residues in the sequence contained one Zn 2+ . Analysis of the CID fragments from the data-independent acquisition (DIA) experiment showed that except the common b 17 fragment, most of them derived from the α-domain (C-terminus).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Interestingly, the y 31 fragment derived from backbone dissociation between α- and β-domain contained three Zn 2+ , probing the higher stability of Zn–S bonds and folding of the α-domain. 14 , 56 On the other hand, fragment b 17 with four Cys residues in the sequence contained one Zn 2+ . Analysis of the CID fragments from the data-independent acquisition (DIA) experiment showed that except the common b 17 fragment, most of them derived from the α-domain (C-terminus).…”
Section: Resultsmentioning
confidence: 99%
“…In our recent study, we attempted to develop an experimental approach that combined native MS and proteomics approaches to elucidate the metal–protein stoichiometry and topology of different Zn 7-x MT2 species. 2 , 14 Having prepared a metal–protein complex (e.g., Zn 4 MT2), the first step is to record mass spectra under nondenaturing conditions. The native-like structure is likely retained because of the kinetic trapping effect, which allowed us to determine the stoichiometry.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations